BCHIRA BEN MRAD: A PIONEER FEMINIST (1913-1993) - Mrad, Bchira Ben (International Journal of Research -GRANTHAALAYAH, 2020)
Can one understand the present without knowing the past? Isn’t life a continuation of the past and doesn’t the present owe many of its characteristics to the past? Asking these questions helps one to figure out how women who lived in a secluded and closed environment were able to break the walls that separated them from the public sphere. It is thus that we come to realize and understand how Bchira Ben Mrad’s (from now on: BBM) initiative in the early 1930s did not start from nowhere but had its origins in the women’s past of her country.